Kinetic theory for chemical reactions without a barrier - Kremer, Gilberto M. (2011)
A new model of the BE for binary reactive mixtures is here proposed with the aim of describing symmetric reversible reactions without a barrier, assuming appropriate reactive cross sections without activation energy and introducing suitable improvements in the elastic and reactive collision terms. The resulting model assures the correct balance equations and law of mass action, as well as good consistency properties for what concerns equilibrium and entropy inequality.Moreover the non-equilibrium effects induced by the chemical reaction on the distribution function are explicitly determined in a flow regime of slow chemical reaction.